The Effect of English Language Film Showing On Listening Ability in Class X Students SMK N 42 Jakarta - Agung Prasetyo; Anita Budi Hayati; Doni Anggoro Ari Santoso; Ira Miranti (Candradimuka: Journal of Education, 2023)
The aim of the study was to find out whether there was an effect of showing English films on listening skills in class X students of SMK Negeri 42 Jakarta. The research method used in analyzing this research is to use quantitative methods. From the results of the homogeneity test, it is known that all data is homogeneous. With the following data: Fcount = 560.96/160.78 = 3.721. So that the data obtained is 3.721 < 4.130 with this then Ho is accepted and it means that the data is homogeneous. The results of the Hypothesis Test are 3.631 > 2.030. Thus, there is an effect of showing English films on listening skills in class X students of SMK Negeri 42 Jakarta. The percentage of success in the final stage reached 76% so that overall the results of this study were that there was an influence of Listening ability on class X students of SMK Negeri 42 Jakarta.